Erdogan’s Politics of Domination: A Critical Discourse Analysis of Neo-Ottomanism - Taufiq, Firmanda; Burdah, Ibnu; Ikhwan, Munirul (AL-TAHRIR, 2024)
Following the dissolution of the Ottoman dynasty in 1924, Turkey experienced profound political transformations. Transitioning from a monarchy under the Ottoman Empire to a republican system under Mustafa Kemal Atatürk, the country embraced secularism as a foundational principle. This article explores the political rhetoric of Recep Tayyip Erdogan, the current President of Turkey, who has revived the concept of Neo-Ottomanism to shape Turkey's developmental trajectory and regional ambitions. By analyzing political statements, policy documents, and public discourses, this study investigates how Erdogan's administration employed Neo-Ottomanism not only to evoke a nostalgic vision of the Ottoman Empire’s grandeur but also as a strategic framework for asserting Turkey's regional influence and political dominance. The article argues that Neo-Ottomanism is a symbolic tool for national identity construction and a practical instrument for projecting geopolitical power.